2013
DOI: 10.3892/ol.2013.1438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Aza-2′-deoxycytidine on the methylation state and function of the WWOX gene in the HO-8910 ovarian cancer cell line

Abstract: The aim of this study was to explore the effects of 5-Aza-2′-deoxycytidine (5-Aza-CdR), a DNA methylation inhibitor, on the methylation state and function of the WWOX gene in the HO-8910 ovarian cancer cell line. The HO-8910 cells were divided into two groups, a control group and a 5-Aza-CdR-treated group. The methylation state of the WWOX gene was evaluated using a methylation-specific PCR assay. The effect of 5-Aza-CdR on the HO-8910 cells was analyzed using MTT and cell invasion assays, as well as flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Moreover, WWOX-negative cases exhibited restored WWOX expression following treatment, and the mean expression level in the WWOX-positive patients was relatively elevated after receiving clinical therapy, indicating that WWOX has the potential to be a candidate predictive marker for treatment. Supporting evidence from another study similarly showed that WWOX protein expression was significantly elevated in the 5-Aza-CdR-treated ovarian cancer group (28). Recently published data indicated that in the treated breast cancer cases with a tumor expressing moderate or strong WWOX protein, recurrence-free survival was improved (29).…”
Section: A B Csupporting
confidence: 64%
“…Moreover, WWOX-negative cases exhibited restored WWOX expression following treatment, and the mean expression level in the WWOX-positive patients was relatively elevated after receiving clinical therapy, indicating that WWOX has the potential to be a candidate predictive marker for treatment. Supporting evidence from another study similarly showed that WWOX protein expression was significantly elevated in the 5-Aza-CdR-treated ovarian cancer group (28). Recently published data indicated that in the treated breast cancer cases with a tumor expressing moderate or strong WWOX protein, recurrence-free survival was improved (29).…”
Section: A B Csupporting
confidence: 64%
“…18 The methyltransferase-specific inhibitor 5-aza-CdR is a pyrimidine analogue whose mechanism is to combine with DNA during DNA replication, form covalent complexes with DNMT1, inhibit the enzyme's methyl transfer activity, produce low-methyl annihilator chains, and reduce the hypermethylation of the gene promoter region to recover gene activity. 19 The study first showed that abnormal methylation of the P16 gene promoter by hyperoxia contributed to the increase of the proliferation of LFs. We then used this hyperoxia-induced BPD mouse model to investigate the activity of 5-aza-CdR in inhibiting the growth and proliferation of LFs.…”
Section: -Aza-cdr Inhibits Fibroblasts Proliferationmentioning
confidence: 99%
“…DZNep and 5‐Aza‐CdR can antagonize tumor cell proliferation, migration, and invasion (Natsume et al, ; Yan et al, ). Our current results in breast cancer cells further validate these findings.…”
Section: Discussionmentioning
confidence: 99%